Biomechanical Changes of Collagen Cross-Linking on Human Keratoconic Corneas Using Scanning Acoustic Microscopy. (3rd May 2016) - Beshtawi, Ithar M.; Akhtar, Riaz; Hillarby, M. Chantal; O'Donnell, Clare; Zhao, Xuegen; Brahma, Arun; Carley, Fiona; Derby, Brian; Radhakrishnan, Hema
ABSTRACT: Purpose : To assess the biomechanical changes of collagen cross-linking on keratoconic corneas in vitro . Methods: Six keratoconic corneal buttons were included in this study. Each cornea was divided into two halves, where one half was cross-linked and the other half was treated with riboflavin only and served as control. The biomechanical changes of the corneal tissue were measured across the stroma using scanning acoustic microscopy (SAM). Results : In the cross-linked corneas, there was a steady decrease in the magnitude of speed of sound from the anterior region through to the posterior regions of the stroma. The speed of sound was found to decrease slightly across the corneal thickness in the control corneas. The increase in speed of sound between the cross-linked and control corneas in the anterior region was by a factor of 1.039×. Conclusion : A higher speed of sound was detected in cross-linked keratoconic corneal tissue when compared with their controls, using SAM. This in vitro model can be used to compare to the cross-linking results obtained in vivo, as well as comparing the results obtained with different protocols.